Nikolai Gogol - Ilchuk, Yuliya (University of Toronto Press, 2021)
One of the great writers of the nineteenth century, Nikolai Gogol was born and raised in Ukraine before he was lionized and canonized in Russia. The ambiguities within his subversive, ironic works are matched by those that surround the debate over his national identity. This book presents a completely new assessment of the problem: rather than adopting the predominant
10.3138/9781487537869
Keywords: Dead Souls; Nikolai Gogol; Russia; Russian empire; Taras Bulba; Ukraine; digital humanities; hybridity; nationalism; othering; performativity; postcolonialism; revisions; stylometric analysis; textology; Ethnicity in literature; National characteristics; Russian; in literature; National characteristics; Ukrainian; in literature; LITERARY CRITICISM / Russian & Former Soviet Union